(untitled) (Baghdad Science Journal, 2025)
Seventy five isolates of Saccharomyces cerevisiae were identified, they were isolated from different local sources which included decayed fruits and vegetables, vinegar, fermented pasta, baker yeast and an alcohol factory. Identification of isolates was carried out by cultural microscopical and biochemical tests. Ethanol sensitivity of the isolates showed that the minimal inhibitory concentration of the isolate (Sy18) was 16% and Lethal concentration was 17%. The isolate (Sy18) was most efficient as ethanol producer 9.36% (v/w). The ideal conditions to produce ethanol from Date syrup by yeast isolate, were evaluated, various temperatures, pH, Brix, incubation period and different levels of (NH4)2HP04. Maximum ethanol produced was 10.32% (v/v). Experimental production of ethanol using continuous methodology with immobilized cells of Saccharomyces cerevisiae showed that this method is superior by producing 5.83 g/L/h in comparison with 1.95 g/l/h produced by batch culture method